Geotechnical properties of waste soil from closed construction dumping area in Serdang, Selangor, Malaysia - Hosni A.A.; Pauzi N.I.M.; Shariffuddin A.S. (E-Journal of Geotechnical Engineering, 2023)
Compaction; Density (specific gravity); Soil surveys; Soils; Atterberg limits; Closed construction dumping area; Compaction test; Geotechnical properties; Maximum dry density; Optimum moisture content; Plasticity indices; Waste soils; Soil testing; Atterberg limit; compaction; dry density; geotechnical engineering; geotechnical property; moisture content; sieving; soil test; Malaysia; Selangor; West Malaysia